LGBTQ+ Young People's Health and Well-being Experiences in Out-of-home Social Care: A scoping review. (December 2022) - Schaub, Jason; Stander, Willem J.; Montgomery, Paul
Highlights: Limited evidence-base examining LGBTQ+ young people's experiences in social care. LGBTQ+ youth have poorer physical and mental health, and well-being outcomes. Ethnic minority LGBTQ+ youth and lesbian/bisexual girls face particular challenges. Social care systems struggle to meet the needs of transgender and nonbinary youth. The field needs more robust research, such as longitudinal and life course studies. Abstract: Background and objectives: The experiences of lesbian, gay, bisexual, transgender, and queer or questioning (LGBTQ+) youth in foster and residential social care have largely been overlooked in research, practice and policy. This scoping review aims to identify and synthesize the existing empirical research concerning the health and well-being needs of LGBTQ+ youth in care. Methods: Following a six-stage approach to scoping reviews, a computerized search was conducted from a total of eight electronic databases: PubMed, Web of Science (Core Collection), Scopus, CINAHL Plus, PsychINFO, Sociological Abstracts, Social Care Online (SCIE), and OpenGrey. Search parameters comprised of three domains (LGBTQ+ status, age, and social care interventions). Data synthesis included thematic analysis, as well as critical appraisal using Critical Appraisal Skills Programme (CASP) criteria. Of the initial 1, 962 sources identified, 22 studies met the search and quality criteria and were included in the final review. Results: Overall, the evidence base is limited with most studies originating from the USA (77 % of included papers). The findings indicate that LGBTQ+ youth experience poorer physical and mental health, and also poorer well-being outcomes compared to non-LGBTQ+ youth while in foster and residential social care. Racial or ethnic minority LGBTQ+ youth, lesbian/bisexual girls, and trans and nonbinary youth face particular challenges, and social care systems appear especially ill-equipped to meet the needs of transgender and nonbinary youth. Conclusion: While the evidence base continues to grow, there remains a need for high quality research including longitudinal and life course studies in various contexts and countries to generate robust empirical evidence in this area. The implications for practice and policy include policy shifts, mandatory and comprehensive competency-based education and training, as well ongoing coaching regarding anti-LGBTQ+ and heteronormative bias within this system.